Interstitial Granulomatous Drug Reaction Due to Chemotherapy - Zhang Q; Chang J (Dove Medical Press, 2023)
Qiuli Zhang, Jianmin Chang Department of Dermatology, Beijing Hospital, National Center of Gerontology, Institute of Geriatric Medicine, Chinese Academy of Medical Sciences, Beijing, People's Republic of ChinaCorrespondence: Jianmin Chang, Department of Dermatology, Beijing Hospital, National Center of Gerontology, Institute of Geriatric Medicine, Chinese Academy of Medical Sciences, No. 1 DaHua Road, Dong Dan, Beijing, 100730, People's Republic of China, Tel +86- 010-85133303, Email changjianmin@medmail.com.cnAbstract: Interstitial granulomatous drug reaction (IGDR) is a drug-related disease with distinctive clinical and histopathological features uncommon in clinical practice. Chemotherapeutics-related IGDR has rarely been reported. Here, we describe one case of interstitial granulomatous drug reaction due to chemotherapy.Keywords: interstitial granulomatous drug reaction, chemotherapy